The Influence of Financial Attitude, Financial Knowledge, and Income on Investment Decisions Mediated by Financial Behavior - Hilman, Dede; Buchory, Herry Achmad (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: Investment decisions are an important aspect to understand in investing. An investment decision is a decision to release funds now with the hope of generating a future cash flow with an amount greater than the funds released at the time of the initial investment. This study aims to analyze the influence of financial attitude, financial knowledge, and income on investment decisions mediated by financial behavior. Methodology: To achieve the research objectives, primary data was used through questionnaires distributed to employees of PT. Citra Niaga Abadi (CNA). The number of samples used in the study was 100 respondents using saturated samples. Path analysis was used as a data analysis method. Finding: The results showed that financial knowledge and financial behavior have a positive effect on investment decisions. However, financial attitude and income have a negative effect on investment decisions. Then, financial attitude, financial knowledge and income have a positive effect on financial behavior. The financial behavior variable is able to moderate financial attitude, financial knowledge and income on investment decisions. Implication: The findings suggest that enhancing financial behavior can be an effective strategy to improve investment decisions, even when financial attitude and income do not directly support positive investment outcomes. Originality: This study uniquely incorporates financial behavior as a mediating variable between financial attitude, financial knowledge, and income in shaping investment decisions—an approach rarely explored in the context of corporate employees.